Perbaikan Sistem “Variable Guide Vane” Gas Turbine SGT-100-S ( Studi kasus di PT.ZZZ ) - Zakaria, Tatan; Lesmana, Sandi (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2016)
PT.ZZZ is a private company electric generation who supply an electrical energy demand to one of paper factory in Tangerang, Banten. The electrical energy generated from gas turbine unit fitted with a synchronous generator. The reliability of electricity supply to the customers is preferred PT.ZZZ, so they have a target of